Immobilisation of Higher Activity Wastes from Nuclear Reactor Production of 99Mo - Martin W. A. Stewart; Eric R. Vance; Sam A. Moricca; Daniel R. Brew; Catherine Cheung; Tina Eddowes; Walter Bermudez (Science and Technology of Nuclear Installations)
A variety of intermediate- and low-level liquid and solid wastes are produced from reactor production of 99Mo using UAl alloy or UO2 targets and in principle can be collectively or individually converted into waste forms. At ANSTO, we have legacy acidic uranyl-nitrate-rich intermediate level waste (ILW) from the latter, and an alkaline liquid ILW, a U-rich filter cake, plus a shorter lived liquid stream that rapidly decays to low-level waste (LLW) standards, from the former. The options considered consist of cementitious products, glasses, glass-ceramics, or ceramics produced by vitrification or hot isostatic pressing for intermediate-level wastes. This paper discusses the progress in waste form development and processing to treat ANSTO’s ILW streams arising from 99Mo. The various waste forms and the reason for the process option chosen will be reviewed. We also address the concerns over adapting our chosen process for use in a hot-cell environment.